2022
DOI: 10.31098/cset.v2i2.583
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Signalizing Application at Unsignalized Intersection Applying Vissim Software Microsimulation

Abstract: An intersection is a meeting point of several road sections that have potential traffic conflicts. Each of these may become the intersection of opposite traffic flows. Therefore, it is critical to have the best traffic control to avoid potential collisions among vehicles. Simpang Jembatan 5 Kalimalang is an unsignalized-intersection with four legs—one of which is a bridge. The absence of traffic control in the intersection may lead to many traffic conflicts. This study aims to determine the best traffic contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…From the two models developed have led to a 75% reduction of the queue length. The Vissim software was used to analyze installation of traffic signal at unsignalized intersection in Bekasi, Indonesia [9]. The study found that replenishing the intersection's two-phased signals with a 106-second cycle time, as an alternative counter condition, was successful in reducing 24% of traffic conflict.…”
Section: Introductionmentioning
confidence: 99%
“…From the two models developed have led to a 75% reduction of the queue length. The Vissim software was used to analyze installation of traffic signal at unsignalized intersection in Bekasi, Indonesia [9]. The study found that replenishing the intersection's two-phased signals with a 106-second cycle time, as an alternative counter condition, was successful in reducing 24% of traffic conflict.…”
Section: Introductionmentioning
confidence: 99%